Honor bound / 2. - London, C. Alexander (Tides of war, 2015)
Petty officer Felix Pratt and Sly, a sea lion in the US Navy's Marine Mammal Program, are deployed to the coast of East Africa--their mission is to assist the Navy Task Force 151 in bringing a dangerous Somali pirate to justice.